Measuring Regional Multipliers: A Comparison between Two Different Methodologies for the Case Of The Italian Regions - Alessandra Faggian; Bianca Biagi (European Regional Science Association (ERSA), 2003)
This paper focuses on theory and methodology in estimating Keynesian regional multipliers. After introducing the concept of Keynesian multipliers at both national and regional level and describe the database used, two methodologies are compared and applied to the case of the Italian regions: the "Marginal propensities method" (MPM) and the "Aggregate leakages method" (ALM). The higher multipliers values in Southern Italy, resulting from the application of both methodologies, are consistent with similar previous findings and appear to be related to the degree of openness of the local economy, the availability of resources and their marginal productivity, the level of wealth, income distribution and the consequent different consumption patterns. Keywords: Keynesian multipliers, Italian regions, regional disparities JEL-classification: R10, E12, R15
Keywords: 330